2014
DOI: 10.1002/ajmg.a.36469
|View full text |Cite
|
Sign up to set email alerts
|

Lymphedema in tuberous sclerosis complex

Abstract: Congenital lymphedema has been described as a possible rare association of tuberous sclerosis complex (TSC), with only six previous cases reported in the literature. TSC is an autosomal dominant, multisystem disorder connected to aberrant regulation of the mammalian target of rapamycin (mTOR) pathway. The aim of this study is to review cases of lymphedema in a large cohort of TSC patients. The medical records of 268 patients seen at The Herscot Center for Children and Adults with Tuberous Sclerosis Complex at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
21
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 25 publications
4
21
1
Order By: Relevance
“…TSC with lymphedema and vascular dysplasia (manifesting as large‐vessel stenosis or aneurysm) has been reported . There are four reports of solitary limb overgrowth , three with vascular anomalies in conjunction with TSC (Table , patients 1–4) .…”
Section: Discussionmentioning
confidence: 99%
“…TSC with lymphedema and vascular dysplasia (manifesting as large‐vessel stenosis or aneurysm) has been reported . There are four reports of solitary limb overgrowth , three with vascular anomalies in conjunction with TSC (Table , patients 1–4) .…”
Section: Discussionmentioning
confidence: 99%
“…This may be related to hormonal influences, as found in other genderbiased manifestations of TSC, including LAM or renal angiomyolipomas (Geffrey, Shinnick, Staley, Boronat, & Thiele, 2014;Hoshiai, Oguma, Sato, Konishi, & Minami, 2015;Navarre & Poitras, 2014;Tan, Tamblyn, & Hinds, 2017).…”
Section: Lymphedemamentioning
confidence: 97%
“…A study including children and adults with TSC found lymphedema in 10 out of 268 patients (4%), and two of those were congenital (Geffrey et al, 2014). A study including children and adults with TSC found lymphedema in 10 out of 268 patients (4%), and two of those were congenital (Geffrey et al, 2014).…”
Section: Lymphedemamentioning
confidence: 99%
“…Tuberous sclerosis complex (TSC) is an autosomal‐dominant, multisystem disorder characterized by benign hamartomas in multiple organ systems. Congenital lymphedema has been described as a possible rare association of TSC . However, there have been very limited reports of imaging evaluation of this clinical condition, and no report of imaging study regarding lymphedema in infants with TSC.…”
mentioning
confidence: 99%
“…Congenital lymphedema has been described as a possible rare association of TSC . However, there have been very limited reports of imaging evaluation of this clinical condition, and no report of imaging study regarding lymphedema in infants with TSC. We evaluated lymphatic function in an extremely low birthweight infant with TSC, using indocyanine green (ICG) lymphography to diagnose and assess the severity of lymphatic dysplasia.…”
mentioning
confidence: 99%